Whatever floats your vote: understanding voter support for public port infrastructure investments. Issue 8 (16th November 2020) - VanCeylon, Jarron; Lang, Corey; Becker, Austin
ABSTRACT: Ports are a cornerstone of the local, state, and national economy, especially for coastal cities. However, ports face growing economic challenges that require infrastructure financing, and a relevant avenue of securing funds is through government assistance via bond issues. We examine voter support for the public financing of port infrastructure investments using a 2016 referendum in Rhode Island. Through our multiple regression voting model, we find strong evidence that public spending on ports in Rhode Island was more of a bipartisan issue compared to other public financing efforts on the ballot. Additionally, neighborhoods with a larger minority presence and those with higher median per capita income were more likely to support port development. In contrast, areas with a higher homeowner population and those communities farther from ports were less likely to support port spending. As a key novelty to our paper, we use our voting model results to forecast how a hypothetical port infrastructure bond might fare in other states, and find that regardless of socioeconomic and political differences, all coastal states in the US would be expected to pass a port referendum.